Effects of mammalian herbivores and termites on the performance of native and exotic plantation tree seedlings. Issue 2 (12th December 2015) - Moe, Stein R.; Loe, Leif Egil; Jessen, Malin; Okullo, Paul
Summary: Invasion of exotic species is a global challenge and the potential for adverse effects on local biodiversity is particularly high in protected areas. Protected African savanna areas support globally important biodiversity. At the same time, forest plantations are widespread throughout Africa and exotic tree species frequently invade natural areas. To evaluate the potential invasiveness of plant species, it is pertinent to know to what extent, if at all, consumption by native herbivore assemblages differentially affects exotic and indigenous plants. We studied how two globally widespread exotic trees Eucalyptus grandis and Grevillea robusta and two common indigenous trees Milicia excelsa and Maesopsis eminii responded to natural herbivory by large herbivores and termites. We experimentally exposed 720 tree seedlings to: (i) no large herbivores or termites; (ii) termites only; (iii) large herbivores only; and (iv) both large herbivores and termites. When exposed to large herbivores and termites, the total survival was much higher for the exotics with 45% ( E. grandis ) and 63% ( G. robusta ) compared to the indigenous species (both 20%). Exposure to large herbivores affected early seedling survival of natives more than the exotics. Apart from the indigenous M. excelsa, survival did not decrease when seedlings were exposed to termites. Large herbivores retarded seedling growth for all species. The exotic E. grandis was the only species capable of growth when exposed to large herbivores. Exposure to termites had only a small, but significant effect resulting in a 7% size difference in all species. Synthesis and applications . Our results highlight how browsing might, for some tree species, adversely affect native seedling survival and growth more than exotic species in protected African savanna. If exotic species are to be used in plantations, managers should consider planting tree species and varieties that are sensitive to ungulate browsing. This will not compromise economic gain because large herbivores are generally less common in plantations. Consequently, local ungulates could function as biological control agents outside plantations and reduce the potential risk of exotic plants proliferating in protected areas. Abstract : Our results highlight how browsing might, for some tree species, adversely affect native seedling survival and growth more than exotic species in protected African savanna. If exotic species are to be used in plantations, managers should consider planting tree species and varieties that are sensitive to ungulate browsing. This will not compromise economic gain because large herbivores are generally less common in plantations. Consequently, local ungulates could function as biological control agents outside plantations and reduce the potential risk of exotic plants proliferating in protected areas.